Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1103/physreve.90.022704
|View full text |Cite
|
Sign up to set email alerts
|

RecA-mediated sequence homology recognition as an example of how searching speed in self-assembly systems can be optimized by balancing entropic and enthalpic barriers

Abstract: Ideally, self-assembly should rapidly and efficiently produce stable correctly assembled structures. We study the tradeoff between enthalpic and entropic cost in self-assembling systems using RecA-mediated homology search as an example. Earlier work suggested that RecA searches could produce stable final structures with high stringency using a slow testing process that follows an initial rapid search of ~9–15 bases. In this work, we will show that as a result of entropic and enthalpic barriers, simultaneously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 37 publications
(38 reference statements)
2
29
0
Order By: Relevance
“…‘Curtains’ of either Rad51- or RecA-coated ssDNA were tethered between nanofabricated barriers, and short fluorescently-labeled duplex oligonucleotides were incubated with the filaments (Figure 4D and Figure 4E). This approach allowed the authors to measure the kinetic lifetimes of the pairing intermediates, and thereby test the model for homology recognition described by Mara Prentiss and colleagues [93, 94]. Interestingly, when dsDNA substrates containing seven nucleotides or less of microhomology were used, the authors saw only transiently paired complexes; however, adding an eighth homologous nucleotide resulted in a dramatic increase in both pairing efficiency and binding energy.…”
Section: Recognition Of Dna Sequence Homology: Testing Involves Concementioning
confidence: 99%
“…‘Curtains’ of either Rad51- or RecA-coated ssDNA were tethered between nanofabricated barriers, and short fluorescently-labeled duplex oligonucleotides were incubated with the filaments (Figure 4D and Figure 4E). This approach allowed the authors to measure the kinetic lifetimes of the pairing intermediates, and thereby test the model for homology recognition described by Mara Prentiss and colleagues [93, 94]. Interestingly, when dsDNA substrates containing seven nucleotides or less of microhomology were used, the authors saw only transiently paired complexes; however, adding an eighth homologous nucleotide resulted in a dramatic increase in both pairing efficiency and binding energy.…”
Section: Recognition Of Dna Sequence Homology: Testing Involves Concementioning
confidence: 99%
“…Interestingly, previous theoretical studies have suggested that the net change in binding free energy for each correctly paired triplet should be on the order of thermal energy (42)(43)(44) and that the fidelity of base triplet pairing during DNA strand exchange would benefit from relatively low changes in binding free energy for each triplet step (42)(43)(44). These studies have also suggested that the structural deformation necessary to extend B-DNA to match the much longer extension of RS-DNA may enhance the ability of the presynaptic complex to reject nonhomologous sequences during the homology search (44 -46).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of length-dependent sequence recognition as a means for rapidly rejecting incorrect sequences was first recognized by Charles Thomas, Jr. (60), who in 1966 suggested that it would be beneficial for recombination to take place between nonrepetitive minimal recognition lengths composed of "words" that can be uniquely identified within the genome, and these original concepts have been further elaborated by several groups (55,(61)(62)(63). Simply put, longer sequences are less common than shorter sequences, so there is a benefit to search for these longer sequences, which will also have a higher probability of being the correct homologous target (Fig.…”
Section: Theoretical Considerationsmentioning
confidence: 99%